Integration of a Geriatric Assessment With Intervention in the Care of Older Adults With Hematologic Malignancies - Wall, Sarah A.; Huang, Ying; Keiter, Ashleigh; Funderburg, Allesia; Kloock, Colin; Yuhasz, Nicholas; Gure, Tanya R.; Folefac, Edmund; Stevens, Erin; Presley, Carolyn J.; Williams, Nicole O.; Krok-Schoen, Jessica L.; et al. (Frontiers in Oncology, 2021)
The incidence of hematologic malignancies (HM) is highest in the seventh decade of life and coincides with increasing occult, age-related vulnerabilities. Identification of frailty is useful in prognostication and treatment decision-making for older adults with HMs. This real world analysis describes 311 older adults with HMs evaluated in a multi-disciplinary oncogeriatric clinic. The accumulation of geriatric conditions (1-unit increase, HR=1.13, 95% CI: 1.00-1.27, p=0.04) and frailty assessed by the Rockwood Clinical Frailty Scale (CFS, mild/moderate/severe frailty v. very fit/well, HR=2.59, 95% CI: 1.41-4.78, p=0.002) were predictive of worse overall survival. In multivariate analysis, HM type (acute leukemia, HR=3.84, 95% CI: 1.60-9.22, p=0.003; myelodysplastic syndrome(MDS)/myeloproliferative neoplasm(MPN)/bone marrow failure, HR=2.65, 95% CI: 1.10-6.35, p=0.03), age (per 5-year increase, HR=1.46, 95% CI: 1.21-1.76, p<0.001), hemoglobin (per 1 g/dL decrease, HR=1.21, 95% CI: 1.05-1.40, p=0.009), deficit in activities of daily living (HR=2.20, 95% CI: 1.11-4.34, p=0.02), and Mini Nutrition Assessment score (at-risk of malnutrition v. normal, HR=2.00, 95% CI: 1.07-3.73, p=0.03) were independently associated with risk of death. The most commonly prescribed geriatric interventions were in the domains of audiology (56%) and pharmacy (54%).The Rockwood CFS correlated with prescribed interventions in nutrition (p=0.01) and physical function (p<0.001) domains. Geriatric assessment with geriatric intervention can be practically integrated into the routine care of older adults with HMs.